Answer:
First one: u = -2
Second one: No solution
Explanation:
-4(u + 3) - 3u = 2(u + 3)
{First distribute the numbers}
-4u - 12 - 3u = 2u + 6
{Then look for like terms on each side and simplify, do this by subtracting 3u from -4u}
-7u - 12 = 2u + 6
{Next make sure like terms are on the same side, do this by subtracting 2u from -7u and adding 12 to 6}
-9u = 18
{Finally, divide both sides by -9 to get the variable, u, by itself}
u = -2
-3(v + 5) + 5v = 2(v - 6)
{First distribute the numbers}
-3v - 15 + 5v = 2v - 12
{Then look for like terms on each side and simplify, do this by adding 5v to -3v}
2v - 15 = 2v - 12
{Next, make sure like terms are on the same side, do this by subtracting 2v from 2v and adding 15 to -12}
0 = 27
{Since 0 is not equal to 27, the equation does not hold to be true and there is no solution as a result}